HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN UPAYA PENCEGAHAN STROKE PADA PASIEN HIPERTENSI DI RUANGAN POLI SARAF RSUD KOTA KOTAMOBAGU - Watung, Grace Irene Viodyta (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p15, 2021)
Stroke is a cut in blood flow to the brain, generally occurs due to rupture of blood vessels to the brain or blockage of blood vessels so that the supply of nutrients and oxygen to the brain is reduced. Stroke causes physical impairment or disability. The study reports that in the last 20 years there has been an increase in the burden of stroke in several European countries by 1.1 million per year in 2000 to 1.5 million per year in 2025. In most cases of stroke, it shows that stroke occurs from an accumulated pattern. life and habits of daily living a day. Stroke prevention efforts are also influenced by the knowledge and attitudes of stroke sufferers. This research uses descriptive analytic method with cross sectional approach. The total population of 30 patients with grade II hypertension was also taken as a total population of 30 patients. Data analysis using Chi Square test. Results: There is a relationship between knowledge and efforts to prevent stroke in hypertensive patients, which is the value of P = 0.000 where the p value is less than p (0.05). There is a relationship between attitude and stroke prevention efforts in hypertensive patients with a value of p = 0.000. As a suggestion: the research site is expected to provide input to improve health services, especially hypertensive patients who are at high risk of stroke. For further research, it is hoped that the research will be better so that the patient's knowledge about the relationship between the knowledge of stroke prevention in hypertensive patients in the neurological clinic of Kotamobagu City Hospital is even better. For health workers at the Nerve Police, they should be active in providing health education about the dangers and prevention of strokes. Keywords: Knowledge, Attitude, Stroke, Hypertension Patients